Dose-response relationships for radiation-related heart disease: impact of uncertainties in cardiac dose reconstruction - Ntentas, G; Darby, SC; Aznar, MC; Hodgson, DC; Howell, RM; Maraldo, MV; Ahmed, S; Ng, A; Aleman, BMP; Cutter, DJ (Elsevier, 2020)
BACKGROUND AND PURPOSE: Radiation-related heart disease (RRHD) can occur many decades after thoracic radiotherapy for Hodgkin lymphoma (HL) or childhood cancer (CC). To quantify the likely risk of RRHD for patients treated today, dose-response relationships derived from patients treated in previous decades are used. Publications presenting these dose-response relationships usually include estimates of uncertainties in the risks but ignore the effect of uncertainties in the reconstructed cardiac doses. MATERIALS/METHODS: We assessed the systematic and random uncertainties in the reconstructed doses for published dose-response relationships for RRHD risk in survivors of HL or CC. Using the same reconstruction methods as were used in the original publications, we reconstructed mean heart doses and, wherever possible, mean left-ventricular doses for an independent case-series of test patients. These patients had known, CT-based, cardiac doses which were compared with the reconstructed doses to estimate the magnitude of the uncertainties and their effect on the dose-response relationships. RESULTS: For all five reconstruction methods the relationship between reconstructed and CT-based doses was linear. For all but the simplest reconstruction method, the dose uncertainties were moderate, the effect of the systematic uncertainty on the dose-response relationships was less than 10%, and the effects of random uncertainty were small except at the highest doses. CONCLUSIONS: These results increase confidence in the published dose-response relationships for the risk of RRHD in HL and CC survivors. This may encourage doctors to use these dose-response relationships when estimating individualised risks for patients-an important aspect of personalising radiotherapy treatments today.